Analysis of Husain Nasr Art Concept on Zafin Dance in the Wedding Tradition of Arabic Descendants in Indonesia - Faizah, Eka Zahrotul; Sholeh, Achmad Khudori; Anisa, Anisa (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to examine the concept of art according to Seyyed Hossein Nasr and its relevance to the art of Zafin Dance which is part of the Arab-Indonesian marriage tradition. This research uses a library research method by examining various sources such as scientific journals, books, and academic papers related to Islamic art philosophy and Arab-Indonesian cultural practices. The main focus of this research is to analyze the aesthetic and spiritual dimensions of the Zafin Dance within the framework of sacred art as described by Nasr. The results of the study show that, first, the concept of art according to Hossein Nasr sees beauty as a reflection of the majesty and beauty of God, which is manifested in the harmony of human movements, rhythms, and expressions. Second, based on the classification of art according to Nasr, the Zafin Dance is classified as a sacred art because it is rooted in spiritual values and has a direct connection with religious traditions. The integration between dance movements and spiritual music makes the Zafin Dance not only entertainment, but also a means of contemplation and a reminder of the Creator. Third, in the Arab-Indonesian marriage tradition, the Zafin Dance has a symbolic meaning as an expression of gratitude and happiness for the marriage, as well as a form of spiritual appreciation that leads people to peace of soul through awareness of the greatness of God and His Messenger. This research confirms that the Zafin Dance functions not only as a performing art, but also as an aesthetic and spiritual expression that represents the unity between beauty, religiosity, and culture in the view of Islamic art as formulated by Seyyed Hossein Nasr.